Bob-1 is expressed in classic Hodgkin lymphoma - Abd El All Howayda S (BMC, 2007)
Abstract Background Almost all researchers agree on the lack of Bob-1 expression in Hodgkin/Reed-Sternberg (H/RS) cells in classic Hodgkin lymphoma (CHL), and utilize this marker as a diagnostic tool in conjunction with other markers to differentiate between lymphocyte predominance Hodgkin lymphoma (LPHL) and CHL. Aim To study the immunohistochemical (IHC) expression of Bob-1 in Egyptian CHL and to correlate this expression with Epstein-Barr virus (EBV) viral load. Materials and methods Paraffin sections of randomly selected 18 CHL cases were included: 2 lymphocyte rich (LR), 4 mixed cellularity (MC), 10 nodular sclerosis (NS) and 2 lymphocyte depletion (LD). All cases were immunostained for Bob-1. EBV was evaluated by EBV early RNA transcripts in situ hybridization (EBER ISH) and immunostaining for EBV latent membrane protein-1 (LMP-1). Results Sixty seven percent of cases (12/18) were positive for EBV by ISH and/or immunostaining for LMP-1. Moderate to strong nuclear Bob-1 was observed in 94% of cases. The positivity ranged between 25-100%. Bob-1 immunoreactivity was strongly associated with EBV positivity (p < 0.001). Conclusion This study proves nuclear IHC expression of Bob-1 on H/RS in CHL implying the difficulties in applying this marker to differentiate between LPHL and CHL. Does this difference between Western and Egyptian CHL reflect genetic and/or environmental factors, or simply no difference exists as most researchers are concentrated on the Western population and no comparative studies have been done. Studies from other countries might answer this question.